Analysis of Worker’s Level of Knowledge on Handling Chemicals in Oil and Gas Industry Laboratory of Pt “X” Indonesia - Dani Nasirul Haqi1, Putri Ayuni Alayyannur1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The oil and gas industry is one of a large-scale industry, which is when carrying out the production process, they contain several hazard posed that can threaten labor, assets, and other people in industrial environment such as chemical hazards. The chemical groups have special characteristics in disturbing and threatening labor. Knowledge is one of the important factors in preventing work accidents and work-related diseases due to chemicals. This study is a descriptive study, and the data was collected by observational. The object of research in this study is knowledge of workers on handling chemicals. The sample is a total population of 28 workers. The results of the research obtained were that most workers already had adequate knowledge regarding handling chemicals in the laboratory. The highest concentration of chemicals in the laboratory is Benzene (19.1 ppm), Toluene (30.56 ppm) and Xylene (20.48 ppm). The conclusion of this study is that knowledge is a very important domain for the formation of a person’s behavior. In this case, it is related to the handling of chemicals found in the laboratory. If the level of knowledge of the workers is high, the handling of chemicals in the workplace can be carried out maximally, so that workplace accidents can be prevented and the safety of workers can be maintained.